Maria Chapdelaine ou le Paradis retrouvé de Gabrielle Gourdeau - analyse de l'hypertexte - Warmuzińska-Rogóż, Joanna (Romanica Silesiana)
The article is an attempt to classify the novel of Gabrielle Gourdeau entitled “Maria Chapdelaine ou le Paradis retrouvé”, which retells the story of the emblematic character of French-Canadian literature (formerly portrayed by Louis Hémon in his novel “Maria Chapdelaine”). With the use of the theory of “hypertext” by Gérard Genette, the author shows that Gourdeau does not merely “continue” Hémon’s narrative but re-visions and re-invents the character of Maria Chapdelaine, by means of such techniques as transposition, transtylization and transvalorization. Key-words: intertextuality; hypertext; the Maria Chapdelaine myth; continuation; transposition